A tiered pathway toward sustainability: The role of public administrators in advancing social equity in U.S. local governments - Cheng, Shaoming and Ali, Susannah (Public Administration Review)
Equity is a central value for public administration as a field and for the advancement of sustainability, yet it is disproportionately and significantly underrepresented and underprioritized in U.S. local governments' sustainability priorities. Equity is referred to as one of the three essential (3z(BEs(3y (Bin sustainability along with environment and economy. Since the first Minnowbrook Conference held in 1968, advancing social equity has become one of the chief goals of public administration as equity emerged as one of the discipline's four (3z(BEs(3y (Balong with economy, efficiency, and effectiveness. In light of this, to what extent are public administrators' concerns and efforts impactful in embracing and advancing social equity in sustainable development? With ICMA's 2015 Local Government Sustainability Practices Survey, this paper offers a unique understanding of localities' tiered realization of sustainability priorities as well as factors correlated with ascending upwards through the tiered pathway of prioritizing sustainability orientation.- Reproduced s